POLITIK TANAH: GERAKAN PERLAWANAN PAGUYUBAN PETANI LAHAN PANTAI KULON PROGO TERHADAP TANAH BERSTATUS PAKUALAM GROUND TAHUN 2016-2018 - Alam Mahadika (Paradigma POLISTAAT: Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
The results of this study indicate that the Kulon Progo Beach Farmers Association belongs to 2 categories, namely the Social Movement and the Agrarian Reform movement, and discussing the Daily Politics in the organization. They are categorizing it as a Social Movement using several indicators, namely: common challenges, common goals, collective solidarity, and collective identity, as well as maintaining resistance politics. In categorizing it as an Agrarian Reform movement based on what the organization stands for. And the last is analyzing the Daily Politics with political themes.